A Systematic Review of Commercial Cognitive Training Devices: Implications for Use in Sport - Harris, David J.; Wilson, Mark R.; Vine, Samuel J. (Frontiers in Psychology, 2018)
Background Cognitive training (CT) aims to develop a range of skills, like attention and decision-making, through targeted training of core cognitive functions. While CT can target context specific skills, like movement anticipation, much CT is domain general, focusing on core abilities (e.g. selective attention) for transfer to a range of real-world tasks, such as spotting opponents. Commercial CT (CCT) devices are highly appealing for athletes and coaches due to their ease of use and eye-catching marketing claims. The extent to which this training transfers to performance in the sporting arena is, however, unclear. Therefore this paper sought to provide a systematic review of evidence for beneficial training effects of CCT devices and evaluate their application to sport. Methods An extensive search of electronic databases (PubMed, PsychInfo, GoogleScholar and SportDiscus) was conducted to identify peer-reviewed evidence of training interventions with commercially available CT devices. 43 studies met the inclusion criteria and were retained for quality assessment and synthesis of results. 17 studies assessed transfer effects beyond laboratory cognitive tests, but only 1 directly assessed transfer to a sporting task. Results The review of evidence showed limited support for far transfer benefits from CCT devices to sporting tasks, mainly because studies did not target the sporting environment. Additionally, a number of methodological issues with the CCT literature were identified, including small sample sizes, lack of retention tests and limited replication of findings by researchers independent of the commercial product. Therefore, evidence for sporting benefits is currently limited by the paucity of representative transfer tests and a focus on populations with health conditions. Conclusions Currently there is little direct evidence that the use of CCT devices can transfer to benefits for sporting performance. This conclusion, however, stems more from a lack of experimental studies in the sporting field and a lack of experimental rigor, rather than convincing null effects. Subsequently, there is an opportunity for researchers to develop more reliable findings in this area through systematic assessment in athletic populations and major methodological improvements.